Gene Expression Analysis in Four Dogs With Canine Pemphigus Clinical Subtypes Reveals B Cell Signatures and Immune Activation Pathways Similar to Human Disease - Raef, Haya S.; Piedra-Mora, Cesar; Wong, Neil B.; Ma, Diana Junyue; David, Clement N.; Robinson, Nicholas A.; Almela, Ramón M.; Richmond, Jillian M. (Frontiers in Medicine, 2021)
Pemphigus is a group of autoimmune-mediated mucocutaneous blistering diseases characterized by acantholysis. Pemphigus has also been recognized in dogs and shares similar clinical characteristics and variants with human pemphigus. While relationships between human and canine pemphigus have been reported, gene expression patterns across species have not been described in the literature. We sought to perform gene expression analysis of lesional skin tissue from four dogs with various forms of pemphigus to examine gene expression during spontaneous disease in dogs. We found increased T and B cell signatures in canine pemphigus lesions compared to controls, as well as significant upregulation of CCL3, CCL4, CXCL10 and CXCL8 (IL8), among other genes. Similar chemokine/cytokine expression patterns and immune infiltrates have been reported in humans, suggesting that these genes play a role in spontaneous disease. Direct comparison of our dataset to previously published human pemphigus datasets revealed five conserved differentially expressed genes: CD19, WIF1, CXCL10, CD86 and S100A12. Our data expands our understanding of pemphigus and facilitates identification of biomarkers for prediction of disease prognosis and treatment response, which may be useful for future veterinary and human clinical trials.